Comparative Study of Inheritance Division According to Munawir Sjadzali and Quraish Shihab - Azhari, Ihsan; Fahrul Razi; Muhammad Fikri; Aminulloh (al-Afkar, Journal For Islamic Studies, 2024)
Basically Islamic law stipulates that the share of a son's inheritance is twice that of a woman's, but the law came down to where in the classical and medieval periods the role of women in the household only revolved around the well, mattress, and kitchen. In contrast to today, where the role of women already has the same rights and obligations in running life in a family. So that contemporary scholars perform ijtihad by relating Islamic law to modern times. The purpose of this study was to find out how comparative the distribution of inheritance according to Munawir Sjadzali and M. Quraish Shihab. This research article uses the librray research method with a descriptive qualitative approach. The results of the study explained the provisions for the distribution of inheritance according to the opinion of Munawir Sjadzali and Quraish Shihab according to a progressive legal perspective, looking at the development of human life itself by adjusting the division of inheritance to 1: 1 by looking at the role roles between women and men who were equal, marriage activities that were dowry in the form of money and gold turned into a set of prayer tools, is a dynamic division with the development of life In this modern-day society, the morals of humanity are put forward for human welfare and happiness in the distribution of inheritance.